EFEKTIFITAS BERBAGAI CARA PEMASAKAN TERHADAP PENURUNAN KANDUNGAN ASAM SIANIDA BERBAGAI JENIS REBUNG BAMBU - Kencana Putra, I Nengah (Agrotekno; Vol. 15, No. 2 Agustus 2009, 2012)
The aim of this research was to find out cyanide acidcontent of some local varieties of bamboo shoot, and to studythe effect of cooking methods on the lowering of the cyanideacid content. The study was done on four local varieties ofbamboo shoot, i.e.: buluh, tabah, tali, and ampel, whereasthe methods of cooking studied were boiling, steaming,boiling with immersing in water previously, and steamingwith immersing in water previously. The results showed thatthe cyanide content of bamboo shoot of ampel, tabah, tali,and buluh variety were 35.76, 22.70, 21.52, and 20.25mg/100g, respectively. Cooking process both boiling andsteaming could reduce cyanide content of the bamboo shoots.Immersing in water for 12 hours before boiling or steamingcould also reduce the cyanide acid content.
Keywords: bamboo shoot, cyanide, cooking, steaming